Effectiveness of a heart disease blended learning program in physiotherapy students: a prospective study - Marques-Sule, Elena; Hernández-Guillén, David; Cezón-Serrano, Natalia; Arjona-Tinaut, Laura; Sillero-Sillero, Amalia; Sánchez González, Juan Luis; Cobos-Rincón, Ana; Juárez-Vela, Raúl; Muñoz-Gómez, Elena (Frontiers in Cardiovascular Medicine, 2023)
Background. In recent years, novel teaching methodologies have been emerging with the aim of improving student learning. One of them is known as Blended Learning. BL allows educators to integrate elements of traditional face-to-face teaching with tailored online learning modalities, integrating the distinct strengths of both methodologies.Purpose. To determine the effectiveness of a heart disease blended learning program in undergraduate physiotherapy students.Methods. 124 participants (average age 21.20 ± 4.67 years, 58.87% female) performed an 8-week heart disease blended learning program that included face-to-face classes and online resources.Knowledge was assessed at baseline, at 4, 8, 12 and 20 weeks. Motivation and engagement were assessed at 4 and 8 weeks. Design of the instructions and learning behaviors were measured at 8 weeks. Finally, 108 subjects completed the study Results. Knowledge significantly increased mid-program (p=0.02), at the end of the program (p<0.001), at 12 weeks (p<0.001) and 20 weeks (p=0.001). After the intervention, a high intrinsic motivation was shown (5.60 ± 0.80)) over 7), whilst extrinsic motivation scored 4.24 ± 0.97 over 7.Finally, engagement (3.98 ± 0.52) over 5), design of the instructions (4.15 ± 0.62) over 5) and learning behaviors (70.51 ± 36.08) downloads, 28.97 ± 16.09) topics visited, and online questionnaires scored 7.67 ± 1.60) over 10) reported adequate scores.This program seems to be an appropriate methodology in future physiotherapists, since it improved knowledge and participants exhibited a high motivation and an adequate engagement, design of the program instructions and learning behaviors.